The Effect of Core Training on Agility in Junior Boxing Athletes - Prabowo, Trisnar Adi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
The purpose of this study was to analyze the effect of core training on the agility of junior category boxing athletes. This type of research is experimental, core training as the experimental group (EG) and control group (CG). The sample was 12 junior boxers divided into 2 groups EG and CG, age characteristics 15.8±4.2 years and training level 2.8±3.7 years. The core training program is 1) Hollow Body Hold, 2) Crawls, 3) Dumbbell Sit Ups, 4) Push Up Walk Out, 5) Sit-up, 6) Spider Walk, 7) Reverse Crunch to Rainbow, 8) Back-up, 9) Med Ball Chops and Twists, 3 - 5 sets, 8 - 12 repetitions, recovery 3 - 6 minutes, intensity 60% - 80%. While the control group is boxers who train routinely. This study was conducted in 18 meetings with 3 meetings each week. Agility test instruments used, Shuttle Run Test, Hexagonal Test, Zig-Zag Run Test. The results, Wilcoxon test (p<0.05) on EG are Shuttle Run Test sig. 0.011; Hexagonal Test sig. 0.008; Zig-Zag Run Test sig. 0.010. While CG is Shuttle Run Test sig. 0.042; Hexagonal Test sig. 0.046; Zig-Zag Run Test sig. 0.042. Mann-Whitney test (p<0.05) is 0.032<0.05, thus EG is recommended as a variation of training to improve agility. Core training has increased agility in junior boxers, then found improvements in stability, coordination, footwork and movement efficiency. In addition, studies found that core training can prevent injury and can be used as an adaptation to intense training. So it will be useful to optimize performance.